2018
DOI: 10.1177/0972150918788748
|View full text |Cite
|
Sign up to set email alerts
|

Firm-specific Parameters and Earnings Management: A Study in the Indian Context

Abstract: This article examines the factors that influence the accrual-based earnings management (AM) and real earnings management (RM) in the Indian context. Different firm-specific parameters as determinants of AM and RM are examined using panel data for 268 listed Indian manufacturing firms for the period 2009–2013. To estimate the AM and RM, Modified Jones Model (Dechow, Sloan, & Sweeney, 1995) and Roychowdhury Model (2006, Journal of Accounting and Economics, 42(3), 335–370) are used, respectively. Findings bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 64 publications
0
13
0
2
Order By: Relevance
“…Such a claim suggests that companies with higher performance possess a higher tendency to manage the companies' earnings. This is proven in Das et al (2018) who found that firm performance, measured using return on assets (ROA), influenced both the accrual-based earnings management and real earnings management for 268 listed Indian manufacturing firms. Aygun et al (2014) also revealed that the ROA is statistically positive significant with earnings management among Turkish firms.…”
Section: Incidence Of Financial Restatementmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a claim suggests that companies with higher performance possess a higher tendency to manage the companies' earnings. This is proven in Das et al (2018) who found that firm performance, measured using return on assets (ROA), influenced both the accrual-based earnings management and real earnings management for 268 listed Indian manufacturing firms. Aygun et al (2014) also revealed that the ROA is statistically positive significant with earnings management among Turkish firms.…”
Section: Incidence Of Financial Restatementmentioning
confidence: 97%
“…The natural logarithm of the firm's years (Kibiya et al, 2016) PERFORM Ratio of ROA (Das et al, 2018) LEVERAGE Ratio of firm's total debt to the firm's total assets (Swai, 2016) LIQUID Ratio of firm's current assets to the firm's liabilities (Somayyeh, 2015) JFC 28,1 have a higher probability of committing financial statement fraud because of the pressure to perform on the management.…”
Section: Agementioning
confidence: 99%
“…These differences may be caused by the different economic situations in the analysed countries, as it is evident that the national environment, economic development, and growth do play a significant role. Das et al (2018Das et al ( , pp. 1240Das et al ( -1260 found that opportunities for corporate growth, financial performance, institutional ownership, and firm age influence earnings management behaviour negatively in Indian enterprises.…”
Section: Overall Assessmentmentioning
confidence: 99%
“…Market returns depict the status of market at the time of issue and hence, to check the influence of market on the relation of listing day return and earnings management the study controls for market returns. A favourable market provide higher listing day returns to the investors as it increases the level of optimism among the investors and issuers (Chhabra et al, 2017;Das et al, 2018;Liu and Lyu, 2016;Lizinska and Czapiewski, 2018;Wijaya et al, 2020) thus, signalling a positive relation between market returns and listing day returns.…”
Section: Jaee 125mentioning
confidence: 99%
“…The size and age of the issuer are characteristics of the issuer that influence policy and the expectations a firm has for its public offering (Sun and Rath, 2009;Naz et al, 2011;Darmadi and Gonawan, 2013;Handa and Singh, 2015;Kouwenberg and Thontirawong, 2016;Bassiouny, 2016) whereas market variables such as time lag and market returns account for market fluctuations at the time of issue and listing (Liu and Lyu, 2016;Das et al, 2018;Chhabra et al, 2017;Lizinska and Czapiewski, 2018;Wijaya et al, 2020). Hence, the study controlled for their effect on listing day returns while determining the influence of earnings management.…”
Section: Descriptive Statistics: Control Variablesmentioning
confidence: 99%